A Review on Optimization Approaches in Cloud Computing Service - E. Jayanthi, V.; Divya, R.; Jagannath, M. (International Journal of Engineering and Technology, 2018)
Cloud has become the best revenue generator tool in the business world. The Cloud Service Provider (CSP) gives importance to the big data arriving in the cloud. Many methodologies are currently available for cloud storage, retrieval and processing. But a discrete solution for all the problems is not possible due to the volume, velocity and variety of data arriving in cloud. Certain best and proved algorithms can be used based on resource utilization, cost pricing, load balancing for the effective utilizations of cloud. The profit based optimization becomes the goal of the CSP. This draws the attention in finding the major factors that influence cloud computing services. In this paper, a detailed survey of optimization techniques for various key factors of cloud are analyzed and the result obtained in each technique is consolidated, tabulated and compared.Â Â